2020
DOI: 10.14740/cr1121
|View full text |Cite
|
Sign up to set email alerts
|

Blood Plasma Resistin and Atrial Fibrillation in Patients With Cardiovascular Disease

Abstract: Background: Atrial fibrillation (AF) affects quality of life and prognosis of patients with cardiovascular disease. Resistin plays an important role in inflammatory response to internal and external factors. The aim of this study is to evaluate the association between resistin and permanent AF (PAF) in patients with cardiovascular disease. Methods: In our study, we included 146 patients with cardiovascular disease. Plasma resistin concentrations and demographic characteristics of patients were recorded. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…A multiethnic cohort study with 1913 participants showed that resistin was an independent risk factor for CAD, MI, and HF but not AF ( 48 ). Two studies suggested that elevated levels of circulating resistin were related to AF, whereas the impact on permanent AF yielded opposite results ( 49 , 50 ). The discrepancy in results may be due to measurement error, residual confounding, or reverse causality in the observational researches.…”
Section: Discussionmentioning
confidence: 99%
“…A multiethnic cohort study with 1913 participants showed that resistin was an independent risk factor for CAD, MI, and HF but not AF ( 48 ). Two studies suggested that elevated levels of circulating resistin were related to AF, whereas the impact on permanent AF yielded opposite results ( 49 , 50 ). The discrepancy in results may be due to measurement error, residual confounding, or reverse causality in the observational researches.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty eight patients with AF presented higher serum resistin levels. 68 There is a practical aspect of measuring resistin levels in epicardial tissue (sectioned during cardiovascular surgery) as that may be an indirect predictor for AF during postoperative care. In our previous study, 46 patients after coronary artery bypass grafting (CABG) were monitored for 3 days after the surgery and divided into 2 groups (with AF after the surgery and without AF after surgery).…”
Section: The Impact Of Resistin Levels On the Etiology Of Atheroscler...mentioning
confidence: 99%
“…In PVAT, adipose tissue is in contact with epicardial coronary arteries. Thus, chronic local inflammation may influence the abnormal development of fibrous tissue and infiltration of conducting tissue [ 16 ].…”
Section: Introductionmentioning
confidence: 99%